Preparation of Hierarchical Structure Au/ZnO Composite for Enhanced Photocatalytic Performance: Characterization, Effects of Reaction Parameters, and Oxidizing Agent Investigations. (18th November 2021) - Vu, Anh-Tuan; Pham, Thi Anh Tuyet; Do, Xuan Truong; Tran, Van Anh; Le, Van Duong; Truong, Duc Duc; Nguyen, The Huu; Nguyen, Minh Viet
Abstract : Zinc oxide (ZnO) has been shown as a potential photocatalyst under ultraviolet (UV) light but its catalytic activity has a limitation under visible (Vis) light due to the wide bandgap energy and the rapid recombination of electrons and holes. Thus, hierarchical structure Au/ZnO composites were fabricated by the hydrothermal method and chemical reduction method for enhanced photocatalytic performance under visible light. As-prepared composites were characterized by UV-vis diffuse reflectance spectra (DR/UV-Vis), field emission scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and electron paramagnetic resonance (EPR). The Au/ZnO-5 composite showed the highest adsorption among as-prepared samples in the range of 250-550 nm, having bandgap energy of 0.13 eV. Au nanoparticles of about 3-5 nm were well dispersed on hierarchical flower ZnO with approximately 10-15  μ m. The EPR signal at g = 1.965 on both ZnO and Au/ZnO samples was attributed to oxygen vacancy Vo, but the presence of Au led to a decrease in signal strength of Au/ZnO composite, showing the degradation efficiency (DE) and reaction rate of 99.2% and 0.109 min -1, respectively; these were larger than those of other samples. The effects of reaction parameters and oxidizing agents on photocatalytic performance were investigated and showed that the presence of H2 O2 and O2 could improve the reaction of composite. In addition, the kinetic and photocatalytic mechanism of tartrazine (TA) on catalysts were studied by the first-order kinetic model and characterized analyses.